Risco e Confiança como determinantes da intenção de consumo de insetos - KÁTIA KATSUMI ARAKAKI (2022)
The success of introducing a new food on the market depends on many factors, because consumer behavior in relation to innovation is a matter of great complexity, because there are several factors that can influence a food choice. These various factors can influence both positively and negatively the intention of innovative food consumption. We emphasize that perceived risk is one of those elements that reduce intention, while trust can have the opposite effect, that is, increase consumption intention. The understanding of how these factors, together, influence a food decision is still a gap. Thus, the question that guides this work is: “What is the relationship between risk perception and consumer confidence in the intention of consuming insects, by the inhabitants of Campo Grande-MS?” Thus, the main objective of this research is to structure an analysis model for risk perception and confidence in the intention of innovative food consumption. Specifically, it seeks to: (i) investigate the relationship between perceived risk and the intention to consume innovative foods, and identify the determinants of perceived risk in the consumption of edible insects; (ii) investigate the relationship between consumer confidence and intention to consume innovative foods; and identify the determining factors of consumer confidence in this consumption; (iii) investigate the relationship between perceived risk and consumer confidence in the intention of innovative food choices; and (iv) to analyze the perception of risk and confidence in the intention to consume insects by the proposed theoretical model, applied to a sample of the capital of the state of Mato Grosso do Sul. Through the systematic review, the theoretical model of perceived risk (its dimensions) and consumer confidence as predictors of insect consumption intention was elaborated, which makes it possible to visualize the variables involved for each of the constructs and their relationships together. This research deals with data collected from consumers in the city of Campo Grande-MS. Data processing took place with the help of Stata 14.0 software, through Confirmatory Factor Analysis and Structural Equation Modeling. As main results, the hypotheses that perceived risk has a negative effect on insect consumption intention and consumer confidence has a positive effect were not rejected. The performance risk dimension is the one that most influences the perception of general risk and not psychological risk. Regarding the 16 trust variables, 11 variables significantly influence consumer trust: recommendation from health professionals, traceability, certification, supermarkets, restaurants, future need, experience, affective memories, involvement, government and television media, with familiarity being a group of great impact. The hypothesis between perceived risk and consumer confidence is not rejected, in the context of innovative food consumption such as edible insects. However, the theoretical model did not present a good fit to the theory, therefore, we proposed an alternative structural approach, which presented a better fit to the theory. Finally, this modeling may indicate an initial path for future research regarding insect consumption intention.